Proteomic changes associated with the development of açaí (Euterpe oleracea Mart.) seeds. Issue 1 (30th July 2022) - Neto, Domingos F. M.; Nascimento, José R. S.; Martins, Gabriel R.; Silva, Ayla S.; Domont, Gilberto B.; Campos, Francisco A. P.; Nogueira, Fábio C. S.
Abstract: Açaí palm ( Euterpe oleracea Mart.) seeds are a rich source of mannans, which can be used to generate bioethanol or be converted to high‐value D‐mannose, in addition to being a source of polyphenols with beneficial health properties. Here, we present a quantitative proteome dataset of açaí seeds at four stages of development (S1, S2, S3, and S4 stages), in which 2465 high confidence proteins were identified and 524 of them show statistically different abundance profiles during development. Several enzymes involved in the biosynthesis of nucleotide‐sugars were quantified, especially those dedicated to the formation of GDP‐mannose, which showed an increase in abundance between stages S1 and S3. Our data suggest that linear mannans found abundantly in endosperm cell walls are initially deposited as galactomannans, and during development lose the galactosyl groups. Two isoforms of alpha‐galactosidase enzymes showed significantly increased abundances in the S3 and S4 stages. Additionally, we quantified the enzymes participating in the central pathway of flavonoid biosynthesis responsible for the formation of catechin and epicatechin, which are subunits of procyanidins, the main class of polyphenols in the açaí seeds. These proteins showed the same pattern of deposition, in which higher abundances were seen in the S1 and S2 stages.